Preparation and properties of thermoplastic sago (Metroxylon sagu Rottb.) starch using different plasticizers - Layan, Hannah Michal Inojales (2011)
This study aims to prepare thermoplastic material from sago starch and evaluate some of its properties namely: tensile strength at break, percentage water absorption and biodegradability. Sago starch was plasticized with glycerol (GLY), diethylene glycol (DEG) and propylene glycol (PG) at concentrations of 20, 30 and 40g/100g starch. Distilled water was also added at a ratio of 4:10 (water: starch). All formulations were subjected to extrusion at 90. 105 and 120 degree Celcius. Thermoplastic sago starch with 20% (w/w) GLY extruded at 90 degree Celcius showed the highest tensile strength value at 2.39MPa. All thermoplastic sago samples extruded at 120 degree Celcius exhibited brittleness, resulting to low tensile strength values. The thermoplastic sago material showed considerably high values for % water absorption, ranging from 7.76 to 28.19%. Moreover, changes in the appearance of the thermoplastic sago samples such as warping and cracking after reconditioning, indicated the large effect of water absorption on the appearance and mechanical strength of the material. The biodegradability of thermoplastic sago material was evaluated based on loss in weight and visible changes after 60 days of burial in ordinary soil and in fortified compost. High total averages of weight loss were observed in ordinary soil condiitions and in fortified compost (40.51) and 59.32% respectively).
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: Thermoplastic starch; Starch; Sago starch; Glycerol; Diethylene glycol; Prpylene glycol